1998
DOI: 10.1145/280265.280267
|View full text |Cite
|
Sign up to set email alerts
|

Elastic time

Abstract: We introduce a new class of synchronization protocols for parallel discrete event simulation, those based on near-perfect state information (NPSI). NPSI protocols are adaptive, dynamically controlling the rate at which processes constituting a parallel simulation proceed, with the goal of completing a simulation efficiently. We show by analysis that a class of adaptive protocols (that includes NPSI and several others) can both arbitrarily outperform and be arbitrarily outperformed by the Time Warp synchronizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 29 publications
0
25
0
2
Order By: Relevance
“…Many other techniques for optimism control have been developed over the last two decades. Examples include the Breathing Time Warp protocol [89], the Global Progress Window algorithm [90], the Elastic Time algorithm [91], and the Switch Time Warp mechanism [92]. Likewise, varied flow-control and learning based algorithms have been defined (see, e.g., [93,94]).…”
Section: Optimism Control Mechanismsmentioning
confidence: 99%
“…Many other techniques for optimism control have been developed over the last two decades. Examples include the Breathing Time Warp protocol [89], the Global Progress Window algorithm [90], the Elastic Time algorithm [91], and the Switch Time Warp mechanism [92]. Likewise, varied flow-control and learning based algorithms have been defined (see, e.g., [93,94]).…”
Section: Optimism Control Mechanismsmentioning
confidence: 99%
“…al., 1994) or performing batch dequeue operations for all processors. (Srinivasan and Reynolds, 1998) showed that near perfect state information protocols could outperform traditional Time Warps systems. They introduced the Elastic Time Algorithm that dynamically adapted to fit the model being simulated.…”
Section: Related Workmentioning
confidence: 99%
“…Adaptive methods based upon global state, as their name implies, rely upon global state to control an LP's progress. The Near Perfect State Information Protocols [32] are a family of protocols which rely on the availability of ''near perfect'' information. One such protocol is the Elastic Time Algorithm [30], in which an LP is slowed down in proportion to the rate at which it moves ahead of its predecessor.…”
mentioning
confidence: 99%